2017
DOI: 10.1115/1.4037860
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Shock Control Using Grooved Surface in a Linear Turbine Nozzle

Abstract: Radial flow variable nozzle turbine (VNT) enables better matching between a turbocharger and engine and can improve the engine performance as well as decrease the engine emissions, especially when the engine works at low-end operation points. With increased nozzle loading, stronger shock wave and clearance leakage flow may be generated and consequently introduces strong rotor–stator interaction between turbine nozzle and rotor, which is a key concern of rotor high-cycle fatigue (HCF) failure. With the purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…To validate this finding, a validation experiment was conducted on a linear turbine with a Schlieren photography system. More detailed information about the measurements and the experimental setup can be found in Lei et al 14 The experimental results expressed herein are only to provide partial validation to the steady CFD simulation.…”
Section: Steady Cfd Simulation and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate this finding, a validation experiment was conducted on a linear turbine with a Schlieren photography system. More detailed information about the measurements and the experimental setup can be found in Lei et al 14 The experimental results expressed herein are only to provide partial validation to the steady CFD simulation.…”
Section: Steady Cfd Simulation and Resultsmentioning
confidence: 99%
“…With the aim of improving the reliability of a radial inflow turbine with nozzle vanes, a method of using a grooved surface on the nozzle vanes was proposed by Sun et al, 11 and, subsequently, more detailed analyses were reported in previous studies. 1215 Following the previous research work, this article investigated the forced response of a turbine wheel by the coupled method of the computational fluid dynamics (CFD) simulations and the finite element analysis (FEA) calculations.…”
Section: Introductionmentioning
confidence: 99%
“…More detailed information about the test rig and validations of numerical simulations can be found in prior publications. 20,21…”
Section: Resultsmentioning
confidence: 99%
“…More detailed information about the test rig and validations of numerical simulations can be found in prior publications. 20,21 Figure 13 also shows the flow characteristics of a shock wave and the leakage flow from the linear nozzle turbine vanes captured by the Schlieren photography system. It is fairly clear that the shock wave originates near the nozzle vane trailing edge and the nozzle endwall clearance leakage flow gradually drifts away from the nozzle vane during flowing downstream.…”
Section: Experimental Validationmentioning
confidence: 99%
“…To meet the rising demand for energy, designing highly efficient turbomachinery systems [1] is an imperative activity. As a result, Oil & Gas companies are now facing major technological changes to improve their mechanical component quality and overall profitability.…”
Section: Introductionmentioning
confidence: 99%